Effetti della densità di preingrasso sull’accrescimento e sulla mortalità di ostriche concave (Crassostrea gigas) in un impianto in long-line - Roncarati Alessandra; Felici Alberto; Magi Gian Enrico; Bilanzcic Nina; GENNARI, Lorenzo (SIRAM, 2017)
A pregrowing trial was carried out using nursery-stage cupped oyster (Crassostrea gigas) in order to evaluate weight, length, mortality, and final costs of spat grown in long-line aquaculture at different sampling times (t1-t5) over 81 days. Spat were reared at two stocking densities in polyvinyl chloride cylinders (10 cm diameter, 24 cm length) placed within lanterns composed of five levels (60 cm diameter, 11 cm height). Each lantern level hosted two cylinders. Lanterns were hung 6 m below the surface of the water in the Middle Adriatic Sea. A total of 53,100 spat (weight 0.033 g, length 5 mm) were divided into 7 cylinders at either high density (H; 5,055 oysters/cylinder, 167.3 g/cylinder) or low density (L; 2,530 oysters/cylinder, 83.7 g/cylinder). On the basis of the ANOVA analysis, spat were significantly heavier (0.352 g vs. 0.227 g; P < 0.001) and longer (12.22 mm vs. 10.47 mm; P < 0.001) in the L group compared to the H group. Considering the time factor, oysters were significantly heavier (0.941 g; P < 0.001) and longer (21.30 mm; P < 0.001) at t5 than at any previous sampling time (t1-t4). A higher rate of mortality was initially observed in the L group (6.7% at t1); however, mortality in the H group was higher at later sampling dates, reaching the highest level at t4 (32.4%). Spat grew better at the low stocking density, demonstrating that a higher stocking density is not suitable.